Castor bean bran in diets for Nile tilapia - Lima, Misleni Ricarte; Ludke, Maria do Carmo Mouhapt Marques; Santos, Elton Lima; Nunes, César Antunes Rocha; Oliveira, Cláudio José Parro (Revista de Ciências Agroveterinárias, 2023)
In fish farming, one of the barriers is the cost of food, which can reach up to 70% of production costs. Faced with this fact, researchers have been looking for solutions to minimize these costs by replacing traditional ingredients with alternative ones. In this sense, the present study aims to evaluate the inclusion of castor bean bran in diets for Nile tilapia fingerlings. We used 144 animals with a mean initial weight of 0.8 ± 0.01 g, distributed in 24 polyethylene aquariums, with a capacity of 80L of water, connected to a recirculation system, in a completely randomized experimental design, consisting of four treatments: 0.0; 3.0; 6.0 and 9.0% of castor bean bran, with six replications each. At the end of the experimental period, final weight, total length, survival rate, weight gain, feed intake, apparent feed conversion, protein efficiency rate, condition factor, and hepatosomatic and liposomatic index. Castor bean bran showed a decreasing linear effect on final weight, total length and weight gain. Thus, the inclusion of castor bean bran in diets for Nile tilapia fingerlings compromised the weight gain of these animals.